Translation, Adaptation and Validation of the European Portuguese Version of the NMS-Quest for Parkinson's Disease - Pedro, Tiago (2021)
Non-motor symptoms are underrecognized features of Parkinson's disease that impair quality of life and increase mortality. In this study, we aim to translate, adapt and validate the European Portuguese version of the "Non-Motor Symptoms Questionnaire", which has proven to be a valid and reliable measurement tool of non-motor symptoms in other languages. Material and Methods: Acceptability was evaluated regarding the range of values, ceiling and floor effects. Reliability was measured in terms of internal consistency (Cronbach’s alpha) and reproducibility (intra-class correlation coefficient). For criterion validity analysis, Movement Disorders Society – Unified Parkinson’s Disease Part I domains’ scores were compared to those of the “Non-Motor Symptoms Questionnaire”. For convergent validity, correlations between the “Non-Motor Symptoms Questionnaire” and the Movement Disorders Society – Unified Parkinson’s Disease Part III, Mini-Mental State Examination score, disease duration, and severity were obtained. Results: Seventy nine Parkinson’s disease patients were recruited, with a mean age of 67.2 ± 10.7 years and a disease duration of 10.8 ± 8.8 years. The European Portuguese version of the “Non-Motor Symptoms Questionnaire” total score was free of significant ceiling and floor effects. With the exception of the cardiovascular domain, adequate overall internal consistency was achieved. The questionnaire domains and the corresponding Movement Disorders Society – Unified Parkinson’s Disease Part I dimensions were significantly correlated, although the total questionnaire score was modestly correlated with disease duration and severity, motor and non-motor symptoms severity and cognitive dysfunction. Discussion: This is the first study to translate, adapt and validate a widely used screening instrument of non-motor symptoms of European Portuguese speaking Parkinson’s disease patients. Conclusion: The European Portuguese version of “Non-Motor Symptoms Questionnaire” is a valid and reliable tool for screening nonmotor symptoms in patients with Parkinson’s disease.